Gaucher's Disease- A case report - Quddush, ASM Ruhul; Md Kamruzzaman, -; Md Badruzzaman, -; Haque, Mirja Hamidul; Ansari, Nazma Parvin; Sattar, Shamima; Parvin, Shabiha; Sultana, Faria (Community Based Medical Journal, 2014)
A 3 years old immunized girl of consanguineous parents presented abdominal distension with hepatosplenomegaly. She was moderately anemic, moderately wasted and stunted. Neurological examination was normal. Musculoskeletal system examination revealed no abnormality. Diagnosis was supported by typical bone involvement in X-ray film (thin cortex in limb bone) and gaucher cell in the bone marrow and also in the splenic aspiration. There are three subtypes Type1: Non neuropathic form, Type 2: Acute neuropathic form, Type 3: Chronic neuropathic form. However some cases do not fit precisely into one of these categories. All forms of Gaucher disease are autosomal recessively inherited. So, this patient more or less correlates with Gaucher disease type 1. Treatment option for type 1 and 3 include medicine and enzyme replacement therapy, which is usually very effective. CBMJ 2014 July: Vol. 03 No. 02 P: 45-48